2000
DOI: 10.1002/(sici)1096-8644(200002)111:2<177::aid-ajpa4>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vertical facial form in patients with severe hypodontia

Abstract: We examined the lateral cephalograms of Russian patients in the following categories: control with acceptable occlusions (group 1); severe hypodontia with absence of six or more teeth (group 2); and severe hypodontia associated with hypohidrotic ectodermal dysplasia (HED) (group 3). Analysis was in a cross-sectional manner, comparing dimensions at the start of the mixed dentition phase (age 6-10) and in the permanent dentition (age 12-18). The groups were matched for age and sex. Thirty-one hard- and soft-tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
60
5
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 11 publications
12
60
5
13
Order By: Relevance
“…Roald et al 35 and Yüksel and Ucem 36 believe that agenesis has a small effect on the dentofacial structure, but Sarnäs and Rune 26 found that morphology and model of growth in children with agenesis are little bit different in regard to children without agenesis. Our findings suggest that there are differences in dentofacial morphology between individuals with tooth agenesis and individuals with complete dentition and normal occlusion, which is consistent with findings of Bondarets and Mc Donald, 24 Ogaard and Krogstad, 25 Wisth et al 27 and Nodal et al…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Roald et al 35 and Yüksel and Ucem 36 believe that agenesis has a small effect on the dentofacial structure, but Sarnäs and Rune 26 found that morphology and model of growth in children with agenesis are little bit different in regard to children without agenesis. Our findings suggest that there are differences in dentofacial morphology between individuals with tooth agenesis and individuals with complete dentition and normal occlusion, which is consistent with findings of Bondarets and Mc Donald, 24 Ogaard and Krogstad, 25 Wisth et al 27 and Nodal et al…”
Section: Discussionsupporting
confidence: 91%
“…3,13,[21][22][23] Craniofacial deviations as retrognathic maxilla, reduced lower face height and increased overbite have also been registered in patients with Bajraktarova Miševska, Cvetanka 1 tooth agenesis. [23][24][25][26][27] Deep bite and Class I skeletal relationship was more frequently found in patients with agenesis than in patients without missing teeth. 28,29 The severity of hypodontia is an important factor in craniofacial morphology.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hypodontia is a congenital absence of 1 or more permanent teeth excluding third molars [1][2][3][4] and it's prevalence varies from 3.5% to 6.5% in permanent dentition, and approximately 1% in primary dentition 5 . Oligodontia or severe hypodontia is defined as a congenital absence of 6 or more teeth excluding the third molars 3,[5][6][7] , which may occur either alone or along with a systemic disorder, such as ectodermal dysplasia 3 .…”
Section: Introductionmentioning
confidence: 99%